(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to identify the effectiveness of the Lorsbach model among first-year middle school students in physics and their critical thinking. In light of this goal، the researcher formulated the following null hypothesis: There is no statistically significant difference at the significance level (0.05) between the average scores of the experimental group students (who study physics using the effectiveness of the Lorsbach model)) and the average scores of the control group students (who study the same subject in the usual way) in the critical thinking test. An experimental design was adopted that includes two groups: an experimental and a control group with a post-test for critical thinking. A purposive sample of (85) students was selected. They were distributed equally into two groups and the equivalence between the students of the two groups was confirmed in terms of chronological age، selection of previous information، previous achievement in science، Raven’s test، and the level of critical thinking. The study material for the year (2024-2025) was selected and the behavioral objectives were determined، amounting to (170) behavioral objectives that are appropriate for the level of first-year middle school students. A daily plan (48) was developed to teach the two groups. Then it was presented to a group of arbitrators to ensure its validity and suitability. The research tool was prepared، which is the critical thinking test، which consists of fourteen fields. Each of them contains (3) paragraphs. The validity of the tool was verified by presenting it to arbitrators in the field of education and physics teaching methods. Reliability was calculated using appropriate statistical methods، as it was calculated by the split-half method before and after correction. As for the Kuder-Richardson 20 method، the results showed that the experimental group that studied the Lorsbach model outperformed the group that studied in the usual way in the critical thinking test. The researcher concluded several recommendations and suggestions that were mentioned in the fourth chapter.